Implementasi Program Pemberian Air Susu Ibu (Asi) Eksklusif di Kota Salatiga - Ike Soraya; Hartuti Purnaweni; Slamet Santoso (Journal of Public Policy and Management Review, 2014)
Based on the high infant mortality rate and low coverage of infants who were exclusively breastfed in Indonesia, the government makes Government Regulation No. 33 2012 on Exclusive Breastfeeding.This research was conducted using descriptive qualitative research method. The location was focused in Puskesmas Sidorejo Kidul and Puskesmas Tegalrejo Salatiga. The selection of informants using purposive sampling. Triangulation techniques used to test the quality of the obtained data.The implementation of this program observed through the implementation stages, goals accuracy, and program performance. Based on the synthesis of Implementation Models of Mazmanian and Sabatier, Hoogwood and Gunn, as well as Merilee S. Grindle, the chosen decisive factors in the program implementation were a power, interests, and strategies of the actors involved; resources deployed; behavior diversity of the target group; as well as compliance and responsiveness.So far, the implementation of exclusive breastfeeding program in Salatiga was not running well because there are still many shortcomings in the implementation stages, goals accuracy, and program performance. Determinant factors in this program implementation can be motivating factor, but also has a potential to be a limiting factos.Recommendations are: (1) dissemination and advocacy on public and private facilities, (2) increase the number of midwives and breastfeeding counselors with the spread arrangements; (3) refer the mother after giving birth to KP ASI ; (4) stronger to supervision against the manufacturer or distributor of infant formula milk; (5) socialized program objectives of exclusive breastfeeding to health professionals and the society , as well as (6) advocacy in the workplace and public facilities with no lactation rooms.